Retrospective Pretest and Counterfactual Self-Report: Different or Same? - Tony C.M. Lam; Edgar Valencia (The Evaluation Center at Western Michigan University, 2019)
Purpose: To examine discriminant validity of treatment participants' self-report of the state they would be in had they not received treatment (counterfactual); specifically, the distinction between self-report of counterfactual and self-report of preintervention state (retrospective pretest).   Setting: An education department of a large University in North America.   Intervention: Methods of self-reporting research self-efficacy with counterfactual items and with retrospective pretest items.   Research design: A randomized comparison group design with two treatments that were defined by the version of the survey used in each. In the survey for the counterfactual condition, items about research self-efficacy without the influence of their program of studies were included. The survey in the retrospective pretest condition contained items regarding research self-efficacy before participating in their program of study. The same items about research self-efficacy at the current time (posttest) were included in both treatment conditions.   Data collection & analysis: Participants were graduate students recruited via email who answered an online survey about research self-efficacy. These students were randomly assigned to one of the two aforementioned treatments. Responses were analyzed using a mixed 2 by 2 randomized factorial ANOVA design with self-report method (counterfactual or retrospective pretest) as the between-subjects factor and time (pre and post intervention) as the within-subjects factor.   Findings: Our findings show that counterfactual and retrospective pretest scores and treatment effects computed based on these two sets of scores are virtually identical, casting doubt on participants' ability to differentiate between a state of no treatment and a state at treatment commencement after they have received treatment.